Assessing agro-meteorological indices and yield performance of groundnut genotypes under varying sowing windows - Paluchani, Meghana Reddy; Thimmegowda, MN; Manjunatha, MH; Mudalagiriyappa; Rajegowda, MB; Jayaramaiah, R; Lingaraj, Huggi; Soumya, DV; Pooja, RS; Arpitha, V (Plant Science Today, 2025)
Groundnut (Arachis hypogaea L.) productivity is highly sensitive to climatic variability. The agro-meteorological assessment is important for getting improvement in yield. The present study was conducted to evaluate the performance of 3 groundnut genotypes namely KCG-6, KL-1812 and K-6 raised under 2 sowing windows (late June and early July) during the Kharif seasons of 2023 and 2024 in field conditions. The results showed that early July sowing led to significantly high pod yield and resource-use efficiency, which is likely due to better thermal and radiation conditions. Among the 3 genotypes, KL-1812 consistently outperformed others, showing superior canopy development, biomass accumulation and pod yield potential. The interaction between genotype and sowing window showed that KL-1812 produced the highest pod yield when sown in late June, indicating that this genotype performed optimally under the environmental conditions associated with this sowing window. Agro-meteorological indices such as growing degree days (GDD), photo-thermal units (PTU) and radiation use efficiency (RUE) were high during July sowing, contributing to better yield performance. In conclusion, the study emphasizes that aligning sowing time and cultivar selection with prevailing weather conditions can significantly enhance groundnut productivity. These findings support the development of climate-smart agricultural strategies and highlight the need for multi-location validation to refine region-specific recommendations.